The Role of Beliefs in Motivating Involvement in Terrorism: a Response to Lorne L. Dawson’s article "Bringing Religiosity Back In: Critical Reflection on the Explanation of Western Homegrown Religious Terrorism (Parts I & II)," Perspectives on Terrorism vol. 15, nos. 1 & 2 (February & April 2021) - Schuurman, Bart (Perspectives on terrorism, 2021)
The causes of involvement in terrorism continue to be subject to a rich academic debate. In several recent contributions, Lorne Dawson, professor of new religious movements, has argued that terrorism researchers too often downplay the role of religious convictions. In setting out his arguments, Dawson has repeatedly referred to some of my own work as an example of this practice. In this article, I respond to Dawson’s criticism in order to show that it does not accurately represent the views that my co-authors and I have put forward. Rather than dismiss the role of ideology, I have argued the need for its contextualization. Extremist beliefs certainly play an important role in motivating and justifying terrorist violence. But they are not sufficient as explanations for such violence because most people who hold extremist views will never act on them. Secondly, even fanatical adherents of extremist beliefs tend to be motivated by more than their convictions alone. Finally, the different degrees of ideological commitment found among terrorists further underline the need to remain critical of the explanatory power of extremist beliefs alone.